Self-Efficacy and Perceived Social Support as Predictors of Subjective Well-Being Among Teachers in an Islamic School Foundation in Gresik (Faculty of Teacher Training and Education Muhammadiyah University of Makassar, 2026)
Objective: This study aimed to examine the contributions of self-efficacy (SE) and perceived social support (PSS) in predicting subjective well-being (SWB) among teachers across early childhood (KB-TK), primary (SD), and lower secondary (SMP) levels at an Islamic educational foundation in Gresik, Indonesia. It addresses the gap in research on teacher well-being across multiple school levels within a single foundation. Method: A quantitative correlational design was applied. From 242 active teachers, 202 respondents were selected via saturated sampling. Data were collected using standardized instruments: Teacher Subjective Well-Being Questionnaire (TSWQ), Teacher Sense of Efficacy Scale (TSES), and Multidimensional Scale of Perceived Social Support (MSPSS). Analyses included descriptive statistics, assumption tests (normality, multicollinearity), and multiple linear regression to assess both simultaneous and partial effects. Results: SE and PSS simultaneously predicted SWB significantly (R = 0.719, R² = 0.516, F(2,199) = 106.2, p < 0.001). Individually, SE (β = 0.526, t = 9.269, p < 0.001) had a stronger effect than PSS (β = 0.293, t = 5.166, p < 0.001). A one-way ANOVA further indicated no significant differences in SWB across educational levels (p > 0.05). The findings suggest that teachers’ SWB remains relatively consistent across school levels. Novelty: This study contributes to the literature by demonstrating that teachers’ subjective well-being is more strongly shaped by internal psychological resources and perceived social support than by differences in educational level. Despite variations in school level, no significant differences in well-being were found, highlighting the role of a shared organizational context in producing relatively uniform well-being across teachers.